Development of CAD/CAM System for Cold Working Closed Die Forging Process - Abdulmawlla, Mohamed A. (2000)
The application of computer-aided engineering (CAE), design (CAD), and manufacturing (CAM), is essential in modern metal forming technology. Thus, process of modelling for the investigation and understanding of deformation mechanics has become a major concern in recent and advanced research, and the finite element method (FEM) has assumed increased importance, particularly in the modelling of deformation processes. This work is devoted to the development of CAD/CAM system for closed die forging process. The system development consists of three stages: namely, metal flow simulation, die failure analysis and design optimisation, and development and implementation of machining code. In the first stage, the finite element method was used to simulate the axisymmetric closed die forging process of copper material. The method was used to study the metal flow, die filling retaining the non-linearity involved in the large change in the geometry, the continuous change in the contact surface condition and the isotropic material work-hardening characteristics. In the second stage, a finite element analysis and optimisation algorithm was developed to examine the die fatigue life and to optimise the die design. The finite element analysis in the first and second stage was carried out using commercially available finite element software called LUSAS. In the third stage, a machining code for the optimised die was developed and implemented using CAD/CAM software called UniGraphics and CNC machine. A qualitative comparison between the computational results and experiments ware made. It had been found that the early stage of the metal flow in closed die forging was very similar to a simple upsetting, then the material flows into the die cavity and towards the flash land leading to a very sharp increase in forging load. The die was designed to sustain the forging load and withstand 1000 load cycles.